Amorphous Fe/Mn bimetal–organic frameworks: outer and inner structural designs for efficient arsenic(iii) removal. Issue 6 (23rd January 2019) - Zhang, Tianshu; Wang, Jing; Zhang, Wentao; Yang, Chengyuan; Zhang, Liang; Zhu, Wenxin; Sun, Jing; Li, Guoliang; Li, Tao; Wang, Jianlong
Abstract : This work describes an amorphous FeMn-MOF-74 adsorbent for the simultaneous removal and detoxication of As(iii ) from aqueous solutions. Abstract : Highly efficient decontamination of naturally occurring As(iii ) from aqueous media remains a rigorous task for public health and ecosystem protection. As its increasingly acute toxicity and mobile characteristics than those of As(v ), it is imperative to exploit a technique for the simultaneous removal and detoxication of As(iii ). Herein, a novel strategy involving outer and inner structural engineering of an amorphous FeMn-MOF-74 adsorbent was developed via a facile temperature-controlled crystallization method, which integrated the inner amorphous structure with low-coordinated active centers and the outer optimized metal atomic ratio with homogeneous adsorption/oxidation sites for generating the synergistic effects of As(iii ) removal. An appropriate Fe/Mn ratio (∼1.96) with optimized temperature (denoted as aFMM-120) endows the synergic effect of iron and high-valence manganese nodes in the framework with the highest experimental adsorption capacity of 161.6 mg g −1 among MOF-based arsenic adsorbents. Detailed characterizations through X-ray photoelectron spectroscopy and Fourier-transform infrared spectroscopy demonstrated the redox behavior of Mn species and surface coordination of oxygen molecules in FeO clusters toward As(iii ). All these results imply that amorphous aFMM-120 is an effective adsorptive oxidation material for efficient arsenic-contaminated water remediation.